Innovative management of the production risks of agricultural enterprises - Hryvkivska, Oksana; Karpinskyi, Roman; Prystеmskyi, Oleksandr; Andrushchenko, Mykola; Namliieva, Natalia (My University, 2024)
The article examines the innovative infrastructure in the management of production risks of agricultural enterprises, which is related to the rules for evaluating alternative scenarios for reducing threats in the production system of agricultural production entities in order to obtain the desired result. A methodical approach to the assessment of factors-tools in the innovative management of production risks, which activate the process of economic development of agricultural enterprises in an institutional environment, is presented. It is proved that the institutional determinants that manage the production risks of agricultural enterprises form a system whose effectiveness depends on the implementation of the relevant directions of economic development of agricultural institutes focused on the introduction of innovations into the production cycle. The structural dialectic connection of the concept of innovative development of agricultural enterprises with the cyclical development of the production system is presented.

У статті досліджено інноваційну інфраструктуру в управлінні виробничими ризиками сільськогосподарських підприємств, яка є пов’язані з правилами оцінки альтернативних сценаріїв зниження загроз у виробничій системі сільськогосподарського виробництва суб'єктів, щоб отримати бажаний результат. Методичний підхід до оцінки факторів-інструментів в інноваційному управління виробничими ризиками, які активізують процес економічного розвитку сільськогосподарських підприємств в інституційне середовище, представлено. Доведено, що інституційні детермінанти управління виробничими ризиками сільськогосподарські підприємства утворюють систему, ефективність якої залежить від реалізації відповідних напрямів діяльності економічний розвиток аграрних інститутів, орієнтований на впровадження інновацій у виробничий цикл. The структурно-діалектичний зв’язок концепції інноваційного розвитку сільськогосподарських підприємств із циклічним представлено розвиток виробничої системи.
Keywords: кафедра економіки і права; investment potential; indicators; criteria; potential life cycle; food industry enterprises; інвестиційний потенціал; показники; критерії; життєвий цикл потенціалу; підприємства харчової промисловості